EVALUATION OF RESISTANCE AGAINST DELTAMETHRIN AND CYPERMETHRIN IN DENGUE VECTOR FROM LAHORE, PAKISTAN - N. Jahan; A. Shahid (Journal of Animal and Plant Sciences, 2013)
The resistance/susceptible status of Aedes aegypti (field strain) from slum area of Misri Shah Lahore, Pakistan was determined during May 2009 to January 2011. Two insecticides i.e. deltamethrin 1.5% EC and cypermethrin 10% EC which were sprayed in various localities of Lahore from the last ten years were used to evaluate resistance/susceptible status of field collected adult females of Aedes aegypti by CDC bottle bioassays. The resistance level was expressed as resistance ratio (RR) of lethal time at 50% death determined using field collected and susceptible strains. Current study indicated RR LT50 1.95 and 1.47 against deltamethrin and cypermethrin in adult females of Aedes aegypti respectively. In addition, the tested population was less resistant against cypermethrin as compared to deltamethrin. In comparison of percent mortalities, there was no significant difference between the two insecticides against adult females.
Keywords: Aedes aegypti; resistance; deltamethrin; cypermethrin; Pakistan